Does crypsis influence foraging patterns in a colour polymorphic Arctic fox population? - Pepels, Kos Jack Johan (UiT Norges arktiske universitet, 2023)
Seasonal coat colour moulting species moult to white winter fur for crypsis in snow-covered landscapes. Seasonal coat colour moulting occurs in birds and mammals; some are colour polymorphic; one of which is the arctic fox (Vulpes lagopus), having a blue and white colour morph. Camouflage, thermoregulation and physiology likely contributed to the evolution of this polymorphism. Climate change is expected to reduce snow cover duration in the Arctic, putting the white morph under pressure as periods of background mismatching may be prolonged. Through behavioural plasticity, animals can select environments that improve their crypsis level, but this mechanism has never been researched in Arctic foxes. Behavioural and phenotypic plasticity are expected to be vital for winter-white morphs to adapt to climate change but remain poorly understood. In this study, I aim to examine whether Arctic foxes are aware of their crypsis level. I thereby build upon the foundations of the camouflage hypothesis to investigate the potential presence of behavioural plasticity linked to crypsis level. I do this through camera trap images from feeding stations on Varanger. I predict conspicuous foxes use feeding stations more because of lowered foraging success (Foraging hypothesis), or alternatively, less to avoid predation at feeding stations (Predator avoidance hypothesis). Furthermore, I predict that conspicuous foxes will display a higher degree of nocturnal behaviour than cryptic foxes to avoid predation (Nocturnal behaviour hypothesis). To investigate this, I analysed 193.715 camera trap images made at 19 feeding stations, scoring 61.950 pictures containing Arctic foxes taken during March, May, August, and December from 2018 until 2021, using the moulting stage, snow cover, and light hours as predictors. I found no compelling evidence to suggest that the two colour morphs use the feeding stations differently. The predicted change in winter detection rate in blue Arctic foxes was not found. Both colour morphs displayed strong ...